Method for preparing magnetic metal nickel gradually-thinned nanowire

The polymer template was prepared by fast heavy ion beam irradiation and ultraviolet sensitization treatment. Combined with asymmetric etching and electrochemical deposition, the problem of complex and low controllability of magnetic metal nickel thinning nanowire preparation in the prior art is solved, and efficient preparation and excellent microwave absorption performance are achieved.

CN119571399AActive Publication Date: 2025-03-07LANZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411850542.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-07
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The prior art is difficult to prepare magnetic metal nickel thinning nanowires simply and efficiently, resulting in complex and low controllability of the preparation method, affecting the high-frequency microwave absorption performance of the magnetic metal nickel thinning nanowire array.

Method used

The polymer template was prepared by fast-heavy ion beam irradiation and ultraviolet sensitization treatment. Combined with asymmetric etching and electrochemical deposition, a template with a thinning linear channel was prepared, and magnetic metal nickel thinning nanowires were prepared on it by electrochemical deposition. Finally, magnetic metal nickel thinning nanowires were obtained by peeling off the gold-copper conductive layer.

Benefits of technology

The efficient preparation of magnetic metal nickel thinning nanowires is achieved. The nanowire diameter varies along the axial gradient, the characteristic size can reach a minimum of 20 nm, and it is not easy to oxidize and cluster, and has excellent microwave absorption performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571399A_ABST
    Figure CN119571399A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing a magnetic metal nickel gradually-thinned nanowire, which comprises the following steps of: (1) irradiating and sensitizing a polymer template by using a fast heavy ion beam to obtain a polymer template with a latent track; (2) sputtering a gold conductive layer on one side of the polymer template of the latent track, and depositing a copper conductive layer on the surface of the gold conductive layer by using electrochemical deposition; (3) etching one side, without the gold-copper conductive layer, of the polymer template of the latent track by adopting an etching solution to obtain a polymer template with a gradually-thinned linear pore channel; (4) electrochemically depositing a magnetic metal nickel gradually-thinned nanowire on one side, without the gold-copper conductive layer, of the polymer template with the gradually-thinned linear pore channel; and (5) stripping the gold-copper conductive layer to obtain the magnetic metal nickel gradually-thinned nanowire. The method is simple and efficient, controllable preparation of the magnetic metal nickel gradually-thinned nanowire array is achieved for the first time, and the small-size magnetic metal nickel gradually-thinned nanowire array with excellent microwave absorption performance is successfully prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic nanomaterials, and in particular to a method for preparing magnetic metal nickel tapering nanowires. Background Art

[0002] While scientific and technological progress is constantly improving the level of social industrialization and intelligence, it has also caused serious electromagnetic wave pollution, which has a great impact on human health, ecological environment and national defense security. Microwave absorbing materials are an effective way to solve various problems such as electromagnetic pollution and interference. Among many electromagnetic functional materials, high-frequency soft magnetic materials have become ideal absorbing materials due to their natural advantages such as good magnetic loss, dielectric loss and high snooker limit, and therefore have received extensive attention and research.

[0003] Many scholars have conducted extensive research in the field of absorbing materials, revealing the relationship between the performance of absorbing materials and novel structures, such as core-shell structures, hollow / porous structures, flower-like structures, foam structures and one-dimensional (1D) structures. These results show that the structure is crucial to regulating the performance of absorbing materials.

[0004] Among them, one-dimensional magnetic nanomaterials, due to their strong shape anisotropy and parallel orientation distribution in the array, can significantly improve the electromagnetic wave absorption performance and are considered to have great potential in the field of electromagnetic wave absorption. Especially for low-symmetry tapered nanowires, the reduction of geometric size and the reduction of symmetry exist simultaneously in magnetic nanostructures, which will inevitably produce novel magnetic phenomena and even enhance application performance.

[0005] There are many methods for preparing one-dimensional magnetic nanostructures, including chemical vapor deposition, sol-gel, electrospinning, arc discharge, molecular beam epitaxy, and template-assisted electrochemical deposition. However, the one-dimensional magnetic nanostructures prepared by the above methods usually have the disadvantages of easy clustering, easy oxidation, uncontrollable geometry, and inability to prepare on a large scale. Therefore, to date, there is still a lack of a simple and efficient method for preparing magnetic metal tapered nanowires. The complexity and low controllability of preparing an ideal low-symmetry tapered nanowire structure have resulted in unclear applications in high-frequency microwave absorption of magnetic metal nickel tapered nanowire arrays. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a simple and efficient method for preparing magnetic metal nickel tapered nanowires.

[0007] In order to solve the above problems, a method for preparing magnetic nickel tapered nanowires according to the present invention comprises the following steps: (1) After the polymer template is irradiated and sensitized by a fast heavy ion beam, a polymer template with a latent track is obtained; (2) sputtering a gold conductive layer on one side of the polymer template of the latent track, and then using electrochemical deposition, with a copper electrode as an anode and the conductive gold layer as a cathode, to deposit a copper conductive layer on the surface of the gold conductive layer; (3) etching the side of the polymer template of the latent track without the gold-copper conductive layer with an etching solution to obtain a polymer template with tapered linear channels; (4) In the polymer template of the tapering linear channel, a Ni electrode is used as an anode and a conductive gold layer is used as a cathode to electrochemically deposit magnetic nickel tapering nanowires; ⑸ Peel off the gold-copper conductive layer to obtain magnetic metal nickel gradually thinning nanowires.

[0008] The material of the polymer template in step (1) is polycarbonate, and its thickness is 12 μm.

[0009] The condition of the fast heavy ion beam irradiation in step (1) is that the heavy ions are xenon ions or tantalum ions, and the irradiation dose is 1×10 8 ions / cm 2 .

[0010] The sensitization condition in step (1) is to sensitize the front and back sides under the ultraviolet sensitization lamp for 10 minutes each, and the sensitization power is 50 mW / cm 2 .

[0011] The duration of sputtering the gold conductive layer in step (2) is 134 s.

[0012] The conditions for electrochemical deposition in step (2) are to use a mixed electrolyte of 75 g / l CuSO4·5H2O and 30 g / l H2SO4 and apply a constant voltage of 0.7 V at room temperature.

[0013] The etching solution in step (3) refers to a mixed solution of methanol and 9 M sodium hydroxide solution uniformly mixed in a volume ratio of 1:9; the etching temperature is room temperature and the etching time is 12±3 min.

[0014] The conditions for electrochemical deposition in step (4) are to use a mixed electrolyte of 250 g / l NiSO4·6H2O, 50 g / l NiCl2·6H2O and 30 g / l H3BO3, and apply a constant voltage of 1.35 V at room temperature.

[0015] A magnetic metal nickel tapered nanowire prepared by the method as described above.

[0016] The magnetic nickel tapered nanowire is characterized in that: the average length of the magnetic nickel tapered nanowire is 10.7±0.4 μm, the minimum wire diameter is 20 nm, and the tapering angle is θ It is 0.58±0.09°.

[0017] Compared with the prior art, the present invention has the following advantages: 1. The present invention prepares magnetic nickel tapered nanowires by combining asymmetric etching and electrochemical deposition with a fast heavy ion track template. The diameter of the obtained nanowires changes gradiently along the axial direction, and the minimum characteristic size can reach 20 nm.

[0018] 2. The preparation method of the present invention is clean, efficient, does not require post-processing, and can be prepared on a large scale.

[0019] 3. The present invention adopts the fast heavy ion track template method to prepare the magnetic metal nickel tapering nanowire array stored in the template without contact with air, so it is not easy to oxidize. The irradiation injection of the fast heavy ion determines the spacing of the magnetic metal nickel tapering nanowires inside the template. The spacing of the magnetic metal nickel tapering nanowires can be controlled by adjusting the irradiation injection, so the prepared magnetic metal nickel tapering nanowires are not easy to cluster.

[0020] 4. The template track irradiated by fast heavy ions in the present invention is uniform and continuous. Combined with asymmetric etching, uniform tapering linear channels can be etched inside the template. The geometric morphology of the magnetic metal nickel tapering nanowires is limited by the size of the channels inside the template. The etching solution composed of methanol and 9 M sodium hydroxide solution can react with the polymer in the track damage area in the fast heavy ion track template. Among them, methanol can perform transverse body etching on the polymer, and sodium hydroxide solution can perform longitudinal track etching on the polymer. Therefore, by controlling the ratio of methanol and sodium hydroxide solution in the etching solution, nanoscale channels with specific geometry can be accurately etched in the polymer template. By selecting templates of different thicknesses, the length parameters of the magnetic metal nickel tapering nanowires can be effectively regulated. Therefore, based on the advantage of strictly controlling the geometric size of the nanostructure, the controllable preparation of magnetic metal nickel tapering nanowires is realized for the first time, and the surface of the resulting tapering nanowires is smooth.

[0021] 5. Compared with other current methods for preparing magnetic nanostructures, the magnetic metal nickel tapered nanowires prepared by the method of the present invention have excellent microwave absorption performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0023] Figure 1 It is a preparation flow chart of the present invention.

[0024] Figure 2The gold conductive layer of the magnetic nickel tapered nanowires of the present invention. Among them: a is a polymer template with a gold spraying time of 134 s; b is a polymer template with a gold spraying time of 268 s; c is a SEM image of the cone tip carrying a residual gold layer when the gold spraying time is 268 s (the scale is 2 μm); d is a SEM image of the cone tip carrying a residual gold layer when the gold spraying time is 268 s (the scale is 15 μm).

[0025] Figure 3 The SEM morphology of the magnetic nickel nanowires of the present invention is shown in Figure 1. a is a single magnetic nickel nanowire; b is an array of magnetic nickel nanowires.

[0026] Figure 4 The figure is a schematic diagram of the SEM geometrical dimensions of a single magnetic nickel tapered nanowire and the length parameters of the magnetic nickel tapered nanowire of the present invention. Among them: a is a schematic diagram of the SEM geometrical dimensions of a single wire; b is a schematic diagram of the definition of the tapering angle; c is the length of the magnetic nickel tapered nanowire (the scale is 5 μm).

[0027] Figure 5 The single SEM morphology statistical characterization of the magnetic metal nickel tapering nanowire of the present invention. Among them: TNW-a is the first single magnetic metal nickel tapering nanowire; TNW-b is the second single magnetic metal nickel tapering nanowire; TNW-c is the third single magnetic metal nickel tapering nanowire.

[0028] Figure 6 The TEM characterization diagram of the magnetic nickel nanowire of the present invention is shown in Figure 1. a is the diffraction ring at the tip of the magnetic nickel nanowire; b is the TEM of the tip of the magnetic nickel nanowire (the minimum diameter can reach 20 nm).

[0029] Figure 7 The electromagnetic parameters of the magnetic nickel nanowires of the present invention are shown in Figure 1. Among them, a is the dielectric constant of the magnetic nickel nanowires; b is the magnetic permeability of the magnetic nickel nanowires.

[0030] Figure 8 This is a graph of microwave reflection loss RL (Reflection Loss) of the magnetic metal nickel tapered nanowires of the present invention.

[0031] Fig. 9This is a performance diagram of the magnetic metal nickel tapered nanowires of the present invention. Among them: Ref.1 is Li Y, Wei H, ChenL, et al. Regulating the Electronic Structure of MAX Phases Based on Rare EarthElement Sc to Enhance Electromagnetic Wave Absorption[J]. ACS Nano, 2024, 18(14): 10019~10030; Ref.2 is Zhang Y, Zhang L, Tang L, et al. S-NiSe / HGNanocomposites with Balanced Dielectric Loss Encapsulatedin Room-TemperatureSelf-Healing Polyurethane for Microwave Absorption and Corrosion Protection[J]. ACS Nano, 2024, 18(11): 8411~8422; Ref.3 is Cheng J, Li Y, Raza H, et al. Cross-Scale Synergistic Manipulation of Dielectric Genes in PolymetallicSulfides from Micropolarization to MacroconductanceToward Wide-Band MicrowaveAbsorption[J]. Advanced Functional Materials, 2024,n / a(n / a): 2405643; Ref.4 is Wu P, Kong X, Feng Y, etc. Phase Engineering on Amorphous / Crystalline γ‐Fe2O3 Nanosheets for Boosting Dielectric Loss and High‐Performance Microwave Absorption[J]. Adv Funct Materials, 2023: 2311983; Ref. 5 is Qian Y, Wu Z, Lv X, etc. Fixed-Point Atomic Regulation Engineered Low-Thickness Wideband Microwave Absorption[J]. Small, 2024, n / a(n / a): 2401878; Ref. 6 is Tang Z, Xu L, Xie C, etc. Synthesis of CuCo2S4@Expanded Graphite with crystal / amorphous heterointerface and defects for electromagnetic wave absorption[J]. Nat Commun, 2023, 14(1): 5951; Ref. 7 is Wen C, Li X, Zhang R, etc. High-Density Anisotropy Magnetism Enhanced Microwave Absorption Performance in Ti3C2T x MXene@Ni Microspheres[J]. ACS Nano, 2022, 16(1): 1150~1159; Ref. 8 is Liu P, Gao S, Wang Y, etc. Carbon nanocages with N-doped carbon inner shell and Co / N-doped carbon outer shell as electromagnetic wave absorption materials[J]. Chemical Engineering Journal, 2020, 381: 122653; Ref. 9 is Liang L, Li Q, Yan X, etc. Multifunctional Magnetic Ti3C2T xMXene / Graphene Aerogel with Superior Electromagnetic Wave Absorption Performance[J]. ACS Nano, 2021, 15(4): 6622~6632; Ref.10 is Wang Y, Qu Z, Wang W, et al. Multidimensional nanomaterialssynergistic polyimide nanofiber / MXene / NiFe2O4hybrid aerogel for high-performance microwave absorption[J]. Chemical Engineering Journal, 2023, 470:144435. DETAILED DESCRIPTION

[0032] like Figure 1 As shown, a method for preparing magnetic metal nickel tapered nanowires comprises the following steps: (1) The polymer template is first irradiated with a fast heavy ion beam, where the heavy ions are xenon ions or tantalum ions, and the irradiation dose is 1×10 8 ions / cm 2 Then sensitize the front and back sides under UV sensitization lamp for 10 minutes each, with a sensitization power of 50 mW / cm 2 After the sensitization, a polymer template with latent tracks is obtained.

[0033] Wherein: the material of the polymer template is polycarbonate, and its thickness is 12 μm.

[0034] ⑵ Sputter a gold conductive layer on one side of the polymer template of the latent track for 134 s. Then, electrochemical deposition was used, with the copper electrode as the anode and the conductive gold layer as the cathode, using a mixed electrolyte of 75 g / l CuSO4·5H2O and 30 g / l H2SO4, and applying a constant voltage of 0.7 V at room temperature to deposit a copper conductive layer on the surface of the gold conductive layer.

[0035] ⑶ Etching the side of the latent track polymer template without the gold-copper conductive layer with an etching solution, wherein the etching solution is a mixed solution of methanol and 9 M sodium hydroxide solution in a volume ratio of 1:9 (ml / ml); the etching temperature is room temperature and the etching time is 12±3 min. After the etching is completed, a polymer template with tapering linear channels is obtained.

[0036] (4) On the side of the polymer template with tapering linear channels without the gold-copper conductive layer, a Ni electrode was used as the anode and the conductive gold layer was used as the cathode. A mixed electrolyte of 250 g / l NiSO4·6H2O, 50 g / l NiCl2·6H2O and 30 g / l H3BO3 was used, and a constant voltage of 1.35 V was applied at room temperature to electrochemically deposit magnetic metal nickel tapering nanowires.

[0037] ⑸ Peel off the gold-copper conductive layer to obtain the magnetic metal nickel gradually thinning nanowires preserved in the polymer template.

[0038] The average length of the magnetic nickel tapered nanowires is 10.7±0.4 μm, the minimum wire diameter is 20 nm, and the tapering angle is θ It is 0.58±0.09°.

[0039] The fast heavy ion track template in the present invention refers to a polymer film having tapering linear nanopores obtained by etching with specific chemical reagents after fast heavy ion irradiation.

[0040] The following is an explanation using PC film as an example.

[0041] Embodiment A method for preparing magnetic nickel tapered nanowires comprises the following steps: ⑴ The fast heavy ion beam accelerated by the accelerator carries high energy and bombards the polymer surface. A large number of chemical bonds in the polymer are broken to form a highly damaged area. From this area, the polymer chain undergoes cross-linking reaction or breaks and reorganizes to form a track structure. The fast heavy ion is xenon ion or tantalum ion, and the irradiation dose is 1×10 8 ions / cm 2 .

[0042] During the UV sensitization of the ion track template, the PC template undergoes photooxidation and photodegradation in the track core region, the polymer chains are cut and release gas, and the polymer fragments are broken to form tiny polymer fragments. Therefore, UV sensitization can improve the etching efficiency of the etching solution on the track region. The UV double-sided sensitization of the latent track template was performed for 10 min each, with a sensitization power of 50 mW / cm 2 .

[0043] ⑵ Use a magnetron sputtering device to sputter a gold conductive layer for 134 s on one side of the latent track polymer template.

[0044] Research has shown that the smaller the diameter at the tip of the magnetic nickel tapering nanowire, the more it helps electromagnetic waves enter the material, ultimately achieving strong absorption of electromagnetic waves by the tapering nanowire. The thickness of the sputtered gold layer plays a crucial role in controlling the diameter at the tip of the tapering nanowire. By controlling the sputtering time and regulating the thickness of the gold conductive layer, the optimal sputtering time parameters are finally obtained. The diameter of the tip of the magnetic nickel tapering nanowire can be as small as 20 nm, laying the foundation for the strong absorption of electromagnetic waves by the magnetic nickel tapering nanowire.

[0045] Figure 2 (ab) are comparison pictures of polymer templates with gold spraying time of 134 s and 268 s. Figure 2 (cd) are SEM images of magnetic nickel tapered nanowires when the gold spraying time is 268 s. As can be seen from the figure, the overly thick gold layer is difficult to remove and remains on the tip of the tapered nanowire. The residual gold layer on the tip of the cone has an adverse effect on the absorption of electromagnetic waves. After a series of comparative experiments, it was finally determined that the gold spraying time of 134 s was the optimal sputtering time parameter for preparing magnetic nickel tapered nanowires.

[0046] Using copper as an electrode, a copper conductive layer was electrochemically deposited on the surface of the gold layer. The copper conductive layer played an auxiliary supporting role for the PC template. A mixed solution of 75 g / l CuSO4·5H2O and 30 g / l H2SO4 was used as the electrolyte, a copper rod was placed as the electrode, a DC voltage of 0.7 V was applied, and the deposition time was about 17 min.

[0047] ⑶ Use an etching solution to etch the side of the latent track polymer template without the gold-copper conductive layer to obtain a polymer template with tapering linear channels.

[0048] Wherein: the etching solution refers to a mixed solution obtained by uniformly mixing methanol and 9 M sodium hydroxide solution in a volume ratio of 1:9 and standing for more than one day; the etching temperature is room temperature and the etching time is 12±3 min.

[0049] Insert the gold rod into the etching solution as an electrode and apply a DC voltage of 0.2 V. Connect the positive and negative electrodes to a 6482 picoammeter (Keithley, USA) to measure the template current in real time. According to the current curve, the etching condition of the conical channel is determined and removed in time. After etching, the remaining etching solution in the deposition tank is sucked out with a rubber dropper and deionized water is injected. The deionized water needs to stay in the deposition tank for five minutes to ensure that there is no etching solution and etching residue in the template channel.

[0050] (4) Electrochemically depositing magnetic metal nickel tapering nanowires on one side of the gold-free copper conductive layer of the tapering linear nanochannel template.

[0051] A mixed deposition solution of 250 g / l NiSO4·6H2O, 50 g / l NiCl2·6H2O and 30 g / l H3BO3 was used. A Ni electrode was used as the anode. A constant voltage of 1.35 V was applied at room temperature, and the deposition current was monitored by a 6482 picoammeter.

[0052] ⑸ Peel off the gold-copper conductive layer to obtain magnetic metal nickel tapered nanowires. Copper and gold have a strong binding force to form a gold-copper conductive layer, and the binding force between the gold conductive layer and the polymer template is weak. Therefore, the gold-copper conductive layer can be removed by mechanically peeling off the copper substrate, so that only the tapered nanowire array and the polycarbonate template that is unresponsive and interference-free to the electromagnetic field exist in the subsequent magnetic measurement.

[0053] The average length of the magnetic nickel tapered nanowires prepared by the above method is 10.7±0.4 μm, the minimum wire diameter is 20 nm, and the tapering angle is θ The SEM morphology of a single nanowire and its array is shown in Figure 3 As shown in Figure 2, the Ni nanocone array is oriented perpendicular to the substrate and arranged in parallel. Figure 4 As shown, the length L of the sample is measured. Three tapering nanowires are randomly selected and divided into three sections, namely, upper, middle and lower. The diameter D of the tapering nanowires is measured by taking regions of the same length ( Figure 5 ), through the formula , calculate the taper angle of the tapered nanowire θ , the results are shown in Table 1.

[0054] Table 1 Geometrical dimensions of magnetic nickel nanowires From the statistical results, it can be seen that the average value of the three-stage tapering angle of a single tapering nanowire is 0.58±0.09°, and the error value is extremely small, indicating that the tapering angle of the magnetic metal nickel nanowire prepared by the template method combined with asymmetric etching and electrochemical deposition can be approximately constant. As the tapering nanowire grows, its diameter increases linearly, and the surface of the tapering nanowire is smooth without mutation. TEM characterization of the tapering nanowire (such as Figure 6 The results show that the tapering nanowires are polycrystalline and have a minimum diameter of 20 nm.

[0055] The electromagnetic parameters of the sample were tested by a vector network analyzer to obtain the magnetic permeability, dielectric constant and reflection loss (RL) data of the tapered nanowires at 2-18 GHz, which were used to evaluate the microwave absorption capacity of the sample.

[0056] Figure 7 a and Figure 7b characterizes the dielectric constant and permeability of the tapering nanowires. The real part represents energy storage, and the imaginary part represents energy loss. There is no obvious peak in the real and imaginary parts of the dielectric constant of the tapering nanowires, and the imaginary value fluctuates in the range of 0-1. The imaginary part of the permeability of the tapering nanowires is relatively flat in the frequency range of 2-8 GHz, and shows an obvious trend of rising first and then falling in 8-18 GHz, and reaches a peak at 16 GHz. The resonance peak of the imaginary part of the permeability represents the resonance loss. Magnetic materials usually lose electromagnetic waves through mechanisms such as hysteresis loss, eddy current loss, natural resonance and exchange resonance. Among them, hysteresis loss is mainly concentrated in the low frequency band, so the contribution of hysteresis loss can be ignored. The nanometer-scale diameter of the tapering nanowires avoids the generation of eddy current loss to the greatest extent. Therefore, it is inferred that natural resonance and exchange resonance are the main magnetic loss mechanisms for microwave absorption of the tapering nanowire array. The electromagnetic waves entering the magnetic metal nickel tapering nanowires are greatly lost through magnetic resonance, achieving excellent microwave absorption performance.

[0057] Using the obtained electromagnetic parameters and based on the transmission line theory, we calculated the reflection loss RL of the magnetic nickel tapered nanowires ( Figure 8 ), the electromagnetic absorption performance of magnetic nickel tapered nanowires was evaluated. An RL value lower than -10 dB means that 90% of the electromagnetic waves are absorbed, and the corresponding frequency absorption range is the effective absorption band EAB. From the three-dimensional reflection loss diagram, it can be seen that the sample with tapered linear nanostructure has good RL loss intensity, and the sample can achieve strong microwave absorption (-50.11 dB / mm) at a low matching thickness. Among them, when the matching thickness is 1.58 mm, the absorption intensity is -79.18 dB, and the absorption bandwidth can reach 6.6 GHz.

[0058] Fig. 9 The microwave absorption performance of magnetic nickel tapered nanowires with a tapering angle of 1° is compared with that of other advanced microwave absorption materials. It can be seen that the microwave absorption performance of magnetic nickel tapered nanowires is not only far superior to similar metal-based microwave absorption materials, but also exceeds most other carbon materials, dielectric materials and composite materials. Its excellent microwave absorption performance comes from the low dielectric loss under the influence of the array structure, the natural advantage of the natural resonance loss of magnetic materials and the strong exchange resonance loss under size modulation, which lays the foundation for the application of magnetic nickel tapered nanowires in the field of microwave absorption.

Claims

1. A method for preparing magnetic nickel nanowires, comprising the following steps: (1) After the polymer template is irradiated and sensitized by a fast heavy ion beam, a polymer template with a latent track is obtained; (2) sputtering a gold conductive layer on one side of the polymer template of the latent track, and then using electrochemical deposition, with a copper electrode as an anode and the conductive gold layer as a cathode, to deposit a copper conductive layer on the surface of the gold conductive layer; (3) etching the side of the polymer template of the latent track without the gold-copper conductive layer with an etching solution to obtain a polymer template with tapered linear channels; (4) Using a Ni electrode as an anode and a conductive gold layer as a cathode on the side of the polymer template without a gold-copper conductive layer in the tapered linear channel to electrochemically deposit magnetic metal nickel tapered nanowires; ⑸ Peel off the gold-copper conductive layer to obtain magnetic metal nickel gradually thinning nanowires.

2. A method for preparing magnetic nickel tapered nanowires according to claim 1, characterized in that: The material of the polymer template in step (1) is polycarbonate, and its thickness is 12 μm.

3. A method for preparing magnetic nickel tapered nanowires according to claim 1, characterized in that: The condition of the fast heavy ion beam irradiation in step (1) is that the heavy ions are xenon ions or tantalum ions, and the irradiation dose is 1×10 8 ions / cm 2 .

4. A method for preparing magnetic nickel tapered nanowires according to claim 1, characterized in that: The sensitization condition in step (1) is to sensitize the front and back sides under the ultraviolet sensitization lamp for 10 minutes each, and the sensitization power is 50 mW / cm 2 .

5. The method for preparing magnetic nickel tapered nanowires according to claim 1, characterized in that: The duration of sputtering the gold conductive layer in step (2) is 134 s.

6. A method for preparing magnetic nickel tapered nanowires according to claim 1, characterized in that: The conditions for electrochemical deposition in step (2) are to use a mixed electrolyte of 75 g / l CuSO4·5H2O and 30 g / l H2SO4 and apply a constant voltage of 0.7 V at room temperature.

7. A method for preparing magnetic nickel tapered nanowires according to claim 1, characterized in that: The etching solution in step (3) refers to a mixed solution of methanol and 9 M sodium hydroxide solution uniformly mixed in a volume ratio of 1:9; the etching temperature is room temperature and the etching time is 12±3 min.

8. The method for preparing magnetic nickel tapered nanowires according to claim 1, characterized in that: The conditions for electrochemical deposition in step (4) are to use a mixed electrolyte of 250 g / l NiSO4·6H2O, 50 g / l NiCl2·6H2O and 30 g / l H3BO3, and apply a constant voltage of 1.35 V at room temperature.

9. A magnetic nickel tapered nanowire prepared by the method as claimed in any one of claims 1 to 8.

10. The magnetic nickel tapered nanowire according to claim 9, characterized in that: The average length of the magnetic nickel tapered nanowires is 10.7±0.4 μm, the minimum wire diameter is 20 nm, and the tapering angle is θ It is 0.58±0.09°.

Citation Information

Patent Citations

  • Method for preparing elliptical magnetic nanowire with large length-diameter ratio and small size

    CN117512595A

  • Polycrystalline cuprous oxide nanowire array production method using low-temperature electrochemical growth

    WO2012093847A2